1988
DOI: 10.1111/j.1365-3059.1988.tb02112.x
|View full text |Cite
|
Sign up to set email alerts
|

The identification of a gene for race‐specific resistance to Peronospora parasitica (downy mildew) in Brassica napus var. oleifera (oilseed rape)

Abstract: The oilseed rape cultivar Cresor was resistant to 14 isolates of Peronospora parasitica derived from crops of Brassica napus in the UK. Segregation for resistance to one isolate among F2 plants and F3 progeny of crosses between Cresor and the susceptible cultivars Victor and Jet Neuf indicated that resistance was controlled by a single gene. There was evidence that genetic background and environment could influence the phenotypic expression of this resistance. Two sexual progeny isolates derived from a homotha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(15 citation statements)
references
References 3 publications
1
13
0
Order By: Relevance
“…Perfection, 9306 F1, 9311 F1 and their resistant parent lines was characterized by restricted sporulation and dark flecking at the inoculation site. The sporulation scores observed in the present study for the resistant material are higher than those previously reported in Brassica lines with resistance based on a single gene ( Natti et al ., 1967 ; Niu et al ., 1983 ; Lucas et al ., 1988 ). Sporulation occurs at high humidity, and differences in humidity may explain differences from sporulation scores reported previously ( Felton & Walker, 1946).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perfection, 9306 F1, 9311 F1 and their resistant parent lines was characterized by restricted sporulation and dark flecking at the inoculation site. The sporulation scores observed in the present study for the resistant material are higher than those previously reported in Brassica lines with resistance based on a single gene ( Natti et al ., 1967 ; Niu et al ., 1983 ; Lucas et al ., 1988 ). Sporulation occurs at high humidity, and differences in humidity may explain differences from sporulation scores reported previously ( Felton & Walker, 1946).…”
Section: Discussionmentioning
confidence: 99%
“…Sporulation occurs at high humidity, and differences in humidity may explain differences from sporulation scores reported previously ( Felton & Walker, 1946). However, the phenotypic host resistance response, characterized by dark, necrotic flecking at the inoculation site, is similar to that previously reported for resistance identified at the cotyledon stage and controlled by a single gene with dominant inheritance ( Natti et al ., 1967 ; Niu et al ., 1983 ; Lucas et al ., 1988 ). Perhaps this type of response is generally related to resistances controlled by single genes, such that the resistance identified in Perfection may also be controlled by a single gene.…”
Section: Discussionmentioning
confidence: 99%
“…Differential responses in B. napus to isolates R1 and P003 were previously grouped in three classes: group 'A' including RES-02, group 'B' which includes 'Cresor', the only oilseed rape cultivar reported to have an isolate-specific gene for resistance to P. parasitica (Lucas et al 1988), and group 'C', including 'Callypso', the susceptible parent in this study for all crosses. The differential response of RES-26 differs from all these (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…Selected plant line RES-02 from group 'A' is resistant to the two isolates. 'Cresor', the only oilseed rape cultivar reported to have an isolate-specific gene for resistance to P. parasitica (Lucas et al, 1988), is in group 'B' and is resistant to isolate R1, but susceptible to isolate P003, whereas group 'C' accessions were susceptible to both isolates (Table 1). Differential responses to P. parasitica expressed at the cotyledon stage have also been reported in other Brassica spp.…”
Section: Introductionmentioning
confidence: 99%
“…The type of genetic control of seedling resistance varies with the source, e.g. one single gene (Natti et al, 1967;Niu et al, 1983;Lucas et al, 1988;Jensen et al, 1999;Farnham et al, 2001), two dominant independent genes (Carvalho & Monteiro, 1996), two or three dominant genes (Moss et al, 1988) and three to four dominant complementary genes (Hoser-Krauze et al, 1995). Resistance at adult-plant stage is governed by a single dominant gene in broccoli (Natti & Atkin, 1960;Barnes, 1968;Coelho & Monteiro, 2003b), in cabbage (Barnes, 1968), and in cauliflower (Mahajan et al, 1995) or by one recessive epistatic gene in cauliflower (Mahajan et al, 1995).…”
Section: Introductionmentioning
confidence: 97%